Oxidative Stress and The Activities of Catalase , GST in Thalassemic Patients - W.F Altai (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
The  study  concentrated  on  measuring  the  lipid  peroxidation marker malon di aldehyde (MDA) in sera of thirty five patients with minor Thalassemia  (Tm), thirty five with major Thalassemia (TM) and thirty five healthy control, their age ranged from (17-30) years. Erythrocytes  enzymes  (Glutathione  -S   - transferase  (GST  )and Catalase) were assayed . The results showed a significant elevation in (MDA) in sera of both patient groups compared to control.